(untitled) (Al-Academy, 2024)
The research deals with the topic of contrast between design thought and applied reality in advertising spaces. Coverage is one of the methods used by the designer for the purpose of showing the shape in an aesthetic way. With the intention of highlighting the aesthetic aspect in it and focusing on it without other forms, this concept may be associated with many and countless aspects in advertising design and as a basis for design thinking and then projecting it onto the reality of the applied side, while invisibility has a great deal of interest in several areas, because of this intellectual system And the applied study has an impact on its study and knowledge of its approaches and methods at the level of statement, disclosure and rhetoric in the presentation and inclusion of ideas and visions by evoking their data and synthesizing them according to rules and principles that embodied creativity in empowerment and expression, which led to the creation of formations capable of expressing hidden contents, as this dialectic revealed dimensions in Language, philosophy and sociology, after showing new dimensions in thought. The research contained four chapters, the first chapter included the methodological framework for the research, and the second chapter came with the theoretical framework, which includes two sections, the concept of concealment philosophically, the concept of invisibility in design, while the third chapter includes research procedures, research methodology, research community, research sample, business analysis, and finally the fourth chapter results Research, conclusions, recommendations, proposals, and Arabic and foreign sources based on the current research, in addition to an Arabic summary and an English summary